2020
DOI: 10.1246/bcsj.20200083
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Diarylthiazol-5-amines: Structure-Specific Mechanofluorochromism and White Light Emission in the Solid State

Abstract: A range of N,N-diarylthiazol-5-amines having a 4-pyridyl group on a thiazole ring were developed, and their photophysical properties were elucidated. Their synthesis was achieved by applying our methods to the combination of N-arylmethyl secondary thioamides and N,N-diarylthioformamides. This enabled us to obtain amines with different types of aromatic groups on the nitrogen atom. Their absorption and emission spectra in solution were examined. The 4-pyridyl group gives higher polarity to the amines. The solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Addition of thioformamides 2 and iodine to the reaction mixture gave 5-aminothiazolines 3 as major products. 44 Further oxidation of 5-aminothiazolines 3 with 2 equivalents of iodine resulted in the formation of the corresponding 5-aminothiazole ligand 4 in low to good yields. Following this reaction, a wide range of substituents possessing electron-donating and -withdrawing properties could be introduced to the 2-, 4-, and 5- positions of the thiazole ring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of thioformamides 2 and iodine to the reaction mixture gave 5-aminothiazolines 3 as major products. 44 Further oxidation of 5-aminothiazolines 3 with 2 equivalents of iodine resulted in the formation of the corresponding 5-aminothiazole ligand 4 in low to good yields. Following this reaction, a wide range of substituents possessing electron-donating and -withdrawing properties could be introduced to the 2-, 4-, and 5- positions of the thiazole ring.…”
Section: Resultsmentioning
confidence: 99%
“…ESI-mass analysis suggested that the zinc atom is coordinated to two bidentate thiazole ligands to form 2 : 1 metal complexes [Zn(L 2 )X 2 ]. 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61,62 In 2020, Murai and coworkers demonstrated the whitelight emission from multi-stimuli-responsive N,N-diarylthiazole-5-amine derivative 30 (Figure 7h). 63 Although only a slight change in the emission properties was observed by grinding pristine orange-emissive solid of 30, the emission color of the ground sample significantly changed to white (CIE coordinate: 0.32, 0.33) upon fuming with acetone. In the emission spectrum of fumed 30, a major peak was observed at 475 nm with a shoulder peak around 600 nm, which resulted in the observation of white light.…”
Section: Directional Control Of Luminescence Wavelengthmentioning
confidence: 99%
“…The stereochemistry on a phosphorus atom has not received much attention, despite the fact that the introduction of at least three different substituents to the phosphorus atom gives rise to the stereogenic center on the phosphorus atom. During the course of our studies on main group chemistry [39,40], we have intensively studied the synthesis and applications studies on main group chemistry [39,40], we have intensively studied the synthesis and applications of organophosphorus compounds with a binaphthyl group [41][42][43][44][45] and recently reported that the deprotonation and alkylation of phosphonoselenoates and phosphonates with a binaphthyl group creates stereogenic secondary and tertiary carbon centers adjacent to the phosphorus atom with high diastereoselectivity (Scheme 1a,b) [46]. The resulting products are potentially available as precursors of primary phosphines since phosphorus-oxygen bonds are readily reduced to P-H bonds.…”
Section: Introductionmentioning
confidence: 99%